2014
DOI: 10.1007/s11605-014-2559-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Postoperative Morbidity and Tumour Response After Neoadjuvant Chemoradiation Followed by Resection for Rectal Cancer

Abstract: Neoadjuvant chemoradiation followed by rectal resection is associated with significant postoperative morbidity but minimal postoperative mortality. A complete response rate of 22% was achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…According to the available data, short‐term outcomes of patients undergoing LAR after neoadjuvant RT are supposed to be less favorable compared to patients without neoadjuvant therapy. In irradiated patients, higher number of peroperative complications (longer operative time, more frequent complications during TME, higher peroperative blood loss) and more frequent postoperative complications have been reported by authors of many available studies …”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…According to the available data, short‐term outcomes of patients undergoing LAR after neoadjuvant RT are supposed to be less favorable compared to patients without neoadjuvant therapy. In irradiated patients, higher number of peroperative complications (longer operative time, more frequent complications during TME, higher peroperative blood loss) and more frequent postoperative complications have been reported by authors of many available studies …”
Section: Discussionmentioning
confidence: 91%
“…A higher number of peroperative complications after neoadjuvant RT implicates technically more demanding surgical preparation during LAR. Irradiated pelvis presents significant factor affecting technical difficulty of surgical dissection during total mesorectal excision . A higher postoperative morbidity of patients after neoadjuvant RT is conditioned mainly by compromised ability of irradiated pelvic tissues to heal and thus technically more demanding TME …”
Section: Discussionmentioning
confidence: 99%
“…In addition, Maggiori et al 57 found the reverse to be true in a group of patients undergoing laparoscopic total mesorectal excision, with fewer major complications, less infection-related morbidity, lower clinical anastomotic leak rates, and shorter LOS in patients with pCR. On the other hand, Duldulao et al 58 and Berkel et al 59 found no significant difference in postoperative complications between patients with pCR compared with non-pCR patients.…”
Section: Discussionmentioning
confidence: 93%
“…The liver-first approach has been reported feasible and safe in several single-centre studies [13][14][15][16][17][18][19]. Since liver metastases are the main cause of death, a liver-first approach means that their elimination is not delayed by treatments directed at the primary tumour or the complications [20]. In the current study we used a modified liver-first approach and performed the liver resection in the time window between radiotherapy and rectal surgery.…”
Section: Discussionmentioning
confidence: 99%